GREEN MARKETING MIX TERHADAP KEPUASAN KONSUMEN PADA PRODUK RAMAH LINGKUNGAN (STUDI KASUS PRODUK THE BODY SHOP DI GRAND MALL BASKO KOTA PADANG) - Saddam Husein Bugis; Lola Fitria Sari; Willy Nofranita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Marketers are investing more in green marketing programs to increase green customer-based brand equity. This study aims to determine the relationship between green marketing mix product (X1), price (X2), promotion (X3), and place (X4) on consumer satisfaction (Y). The population in this study are consumers who buy The Body Shop products at Grand Mall Basko Padang City in 2021 as many as 443 respondents. The number of samples in this study was 180 respondents. Observational data were processed using the Structural Equation Modeling (SEM) method with the Stata 17 program. The partial test results in this study showed that green products has an effect on green prices. Green price affects consumer satisfaction. Green product has an effect on consumer satisfaction. Green product affects on green promotion. Green promotion affects consumer satisfaction. The green promotion affects on green place and green place also shows a positive and significant value on consumer satisfaction. A green marketing mix is very important to achieve the level of consumer satisfaction with the company's products because companies face increased public sensitivity, tighter regulations, and increasing stakeholder pressure to focus on preserving the natural environment.Keywords: Green Product, Green Price, Green Promotion, Green Place, Consumer Satisfaction.